2008
DOI: 10.1007/s10840-008-9243-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of contrast enhanced 64-slice computed tomography and transesophageal echocardiography in detection of left atrial thrombus in patients with atrial fibrillation

Abstract: Compared to gold standard TEE, 64CCT was shown to be less reliable in the detection of LA/LAA thrombus prior to catheter ablation in patients with AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 6 publications
1
35
0
Order By: Relevance
“…Similarly, Hur et al [13] found a sensitivity and specificity of 89% and 100%. In contrast, Tang et al [10] conclude from CCT sensitivity and specificity of 36.4% and 93.7% that both modalities are necessary. Variation in results can partially be explained by inconsistency in CCT and TEE methodology.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Similarly, Hur et al [13] found a sensitivity and specificity of 89% and 100%. In contrast, Tang et al [10] conclude from CCT sensitivity and specificity of 36.4% and 93.7% that both modalities are necessary. Variation in results can partially be explained by inconsistency in CCT and TEE methodology.…”
Section: Discussionmentioning
confidence: 90%
“…Current literature includes both prospective and retrospective cross-sectional studies, and a meta-analysis [5,[7][8][9][10][11][12][13]18]. Study sizes have varied from 72 to 402 patients [7,9], yet current literature remains controversial.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, transesophageal echocardiography is semi-invasive. Multidetector cardiac CT is emerging as a powerful diagnostic tool to detect LAA thrombosis (Kim et al, 2007, Shapiro et al, 2007, Singh et al, 2009, Tang et al, 2008, Tani et al, 2003. Tani et al evaluated the usefulness of CT for detecting LAA thrombi in patients with chronic atrial fibrillation as compared to transesophageal echocardiography (Tani et al, 2003).…”
Section: Ct Imaging To Diagnose Laa Thrombosismentioning
confidence: 99%